2021
DOI: 10.1177/14680874211013667
|View full text |Cite
|
Sign up to set email alerts
|

Potential of reactivity-controlled compression ignition with reverse reactivity stratification (R-RCCI) fueled with gasoline and polyoxymethylene dimethyl ethers (PODEn)

Abstract: To improve the trade-off between thermal efficiency and peak heat release rate (HRR) of partially premixed combustion (PPC) and the combustion efficiency of reactivity-controlled compression ignition (RCCI), the combustion mode with premixed high-reactivity fuel and direct-injection (DI) low-reactivity fuel, called RCCI with reverse reactivity stratification (R-RCCI), was explored at low loads in a light-duty diesel engine in this study. Compared with diesel, polyoxymethylene dimethyl ethers (PODEn) has better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…1 shows the molecular structures of PODE 1 , PODE 2 and PODE 3 . The chain structure of PODE n featuring the C-O bond ensures its high oxygen content (nearly 50%), and as such generates less soot emissions in combustion [ 4 , 5 ]. Researchers found that PODE 2-5 have similar physical properties to diesel fuel, and PODE 2-5 is stable and mutually soluble with diesel fuel at room temperature [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the molecular structures of PODE 1 , PODE 2 and PODE 3 . The chain structure of PODE n featuring the C-O bond ensures its high oxygen content (nearly 50%), and as such generates less soot emissions in combustion [ 4 , 5 ]. Researchers found that PODE 2-5 have similar physical properties to diesel fuel, and PODE 2-5 is stable and mutually soluble with diesel fuel at room temperature [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%